2012
DOI: 10.1007/s10562-012-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation and Ring Opening of Aromatic and Naphthenic Hydrocarbons Over Noble Metal (Ir, Pt, Rh)/Al2O3 Catalysts

Abstract: The hydrogenation and ring opening of model hydrocarbons and of naphtha was studied over commercial noble metal (Ir, Pt, Rh)/Al 2 O 3 catalysts. The experiments were performed in a fixed bed reactor at temperatures between 220 and 350°C and pressures of 1.1 and 5.0 MPa, respectively. The product distribution was determined and the cetane number was calculated. The Pt catalyst is very active for hydrogenation of aromatics but does not catalyse the ring opening of naphthenes. The Ir and Rh catalysts are active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…In addition, several direct ring opening pathways for methylcyclohexane without any cyclopentane intermediates have also been proposed in the literature. 23,24 As expected, similar pathways for hydrogenation and ring opening of toluene have been proposed in the literature. 24,25 Methylcyclohexane has been reported as the most abundant intermediate, which is the direct hydrogenation product from toluene.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, several direct ring opening pathways for methylcyclohexane without any cyclopentane intermediates have also been proposed in the literature. 23,24 As expected, similar pathways for hydrogenation and ring opening of toluene have been proposed in the literature. 24,25 Methylcyclohexane has been reported as the most abundant intermediate, which is the direct hydrogenation product from toluene.…”
Section: Introductionsupporting
confidence: 81%
“…23,24 As expected, similar pathways for hydrogenation and ring opening of toluene have been proposed in the literature. 24,25 Methylcyclohexane has been reported as the most abundant intermediate, which is the direct hydrogenation product from toluene. The product from methyl group eliminationbenzenehas also been observed.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The use of catalysts is key for producing clean fuels and several commodities, particularly by means of hydrogenation reactions of CC double bonds in olefins, where Pt, Pd, Ru, Rd, Os, and Ir sometimes termed Pt-group elements are so far the most used catalyst due to their good performance . In practice, these metals are supported on oxides, zeolites, and activated carbon, and exhibit a high catalytic activity. However, the scarcity of these metals in the Earth’s crust, together with their sensitivity to sulfur poisoning in the petrochemical industry, has motivated the search for alternative catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Last, the benzene-H 2 reaction formed cyclohexane as the only hydrogenation product, at a selectivity of 74.6%, and C1–C6 hydrocarbons (except cyclohexane) from ring contraction and/or hydrocracking, at a selectivity of 25.4%. Although few studies have reported the reaction pathway of benzene hydrocracking on metallic Ru catalysts, we surmise that the hydrocracking occurs readily after the benzene hydrogenation on Ru 0 /SiO 2 , since previous studies for benzene, toluene, propylbenzene, and m -xylene hydroconversion over transition metal catalysts (Ir/Al 2 O 3 and Rh/Al 2 O 3 ) under comparable conditions (493–553 K, 1.1 MPa) have reported that the hydrogenation events, which generate cyclic alkanes, occur before the hydrogenolysis events …”
Section: Resultsmentioning
confidence: 77%